Kawasan Rumah Pangan Lestari sebagai Upaya Peningkatan Ketahanan Pangan Masyarakat Pada Masa Pendemi Covid-19 - Nurholis Nurholis (LPPM Universitas Trunojoyo Madura, 2021)
Food is anything that comes from biological sources, for example from agricultural, plantation, forestry, fishery and livestock products, both processed and unprocessed which are intended as food or drink for public consumption. The condition of the fulfillment of food for households or the community is reflected in the availability of sufficient food, in quantity, quality, and safe for consumption. In order to achieve food security, food self-sufficiency is needed, namely the ability to provide food from one's own production or independently by utilizing the yard at the household level. Therefore, it is necessary to develop a Sustainable Home Food Area Model (KRPL Model) to optimize the use of yard land which can later meet the food and nutritional needs of the family which in turn will improve the welfare of the community. This activity took place during the implementation of the UTM KKN for the July 2020 period. The activities carried out consisted of introducing the KRPL concept, training, and assistance in managing yards at the household level so that the results of this activity can develop the ability of families and communities economically and socially in meeting needs. food and nutrition in a sustainable manner, leading to a prosperous family and community